Patients with paroxysmal nocturnal hemoglobinuria demonstrate a prothrombotic clotting phenotype which is improved by complement inhibition with eculizumab. Issue 8 (11th May 2020) - Macrae, Fraser L.; Peacock‐Young, Barnaby; Bowman, Polly; Baker, Stephen R.; Quested, Sam; Linton, Emma; Hillmen, Peter; Griffin, Morag; Munir, Talha; Payne, Daniel; McKinley, Claire; Clarke, Deborah; et al.
Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematological disorder, characterized by complement‐mediated intravascular hemolysis and thrombosis. The increased incidence of PNH‐driven thrombosis is still poorly understood, but unlike other thrombotic disorders, is thought to largely occur through complement‐mediated mechanisms. Treatment with a C5 inhibitor, eculizumab, has been shown to significantly reduce the number of thromboembolic events in these patients. Based on previously described links between changes in fibrin clot structure and thrombosis in other disorders, our aim was to investigate clot structure as a possible mechanism of thrombosis in patients with PNH and the anti‐thrombotic effects of eculizumab treatment on clot structure. Clot structure, fibrinogen levels and thrombin generation were examined in plasma samples from 82 patients from the National PNH Service in Leeds, UK. Untreated PNH patients were found to have increased levels of fibrinogen and thrombin generation, with subsequent prothrombotic changes in clot structure. No link was found between increasing disease severity and fibrinogen levels, thrombin generation, clot formation or structure. However, eculizumab treated patients showed decreased fibrinogen levels, thrombin generation and clot density, with increasing time spent on treatment augmenting these antithrombotic effects. These data suggest that PNH patients have a prothrombotic clot phenotype due to increased fibrinogen levels and thrombin generation, and that the antithrombotic effects of eculizumab are, in‐part, due to reductions in fibrinogen and thrombin generation with downstream effects on clot structure.